Science communication in times of crisis - Hohaus, Pascal (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2022)
"This volume addresses demands on external and internal science communication in times of crisis. The contributions discuss present crises such as COVID-19 (e.g. vaccination campaigns or political reactions towards the pandemic in the context of science scepticism), and climate change (e.g. plausibility judgements or the role of scientists). They also relate their approaches to past crises, e.g. 9/11 or the Galileo affair. This volume is unique in that it is interdisciplinary from a theoretical and methodological perspective. In that respect, the authors apply concepts from corpus linguistics, discourse analysis, rhetoric, news values analysis, pragmatics and terminology research to various types of data, such as newspaper headlines, Tweets, open letters, corpora or glossaries. The case studies are situated within different cultural contexts, with various languages being examined, i.e. Polish, Arabic, English, French, German, and Spanish. Elevating our understanding of the interface of science communication and crisis communication, this collection of articles proves valuable to scholars and students from linguistics, communication science, political science, sociology and philosophy of science"--
Communicating science in crisis societies : challenges across disciplines, contexts and nations / Pascal Hohaus -- Which facts to trust in the debate on climate change? On knowledge and plausibility in times of crisis / Martin Böhnert and Paul Reszke -- Letters to power : authority appeals in the communication of scientific consensus / Collin Syfert -- Pivoting to support science communication in times of crisis : a case study of the government of Canada's glossary on the COVID-19 pandemic / Lynne Bowker -- COVID-19 neologisms between metaphor and culture : a multilingual corpus-based study / Amal Haddad Haddad -- Persuasion in health communication : the case of Saudi and Australian tweets on COVID-19 vaccination / Dina Abdel Salam El-Dakhs -- Communicating risks of an anti-COVID-19 vaccine in Poland : a comparative case study of content, style and advocacy of three media outlets / Katarzyna Molek-Kozakowska and Sofiia Struchkova -- 'Coronavirus as a political weapon' : the COVID pandemic through the lens of the US alt-right media / Zeynep Cihan Koca-Helvacı -- Science versus? The U.S. response to the COVID-19 pandemic / John M. Callahan and Robert Jensen.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Communication in science -- Case studies; Communication in crisis management -- Case studies; Truthfulness and falsehood; COVID-19 Pandemic, 2020-2023 -- Social aspects; COVID-19 Pandemic, 2020-2023 -- Political aspects; Information scientifique -- Études de cas; Communication en gestion de crise -- Études de cas; Pandémie de COVID-19, 2020-2023 -- Aspect social; Pandémie de COVID-19, 2020-2023 -- Aspect politique; LANGUAGE ARTS & DISCIPLINES / Linguistics / Pragmatics; Truthfulness and falsehood; Social aspects; Communication in crisis management; Communication in science; Since 2020; Case studies